2021
DOI: 10.4236/cc.2021.92006
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Determination of Influence of the Metallic State of Oxidation toward Cytotoxic Activity: Case of Ruthenium Complexes

Abstract: Ruthenium complexes present two states of oxidation that are Ru(II) and Ru(III). Both are assumed to present cytotoxic activity at ground state. On the purpose of highlighting their differences, DFT, TD-DFT and NBO have been performed at both Wb97xd/Lanl2dz and B3lyp/Lanl2dz levels. NBO program shows that both groups of ruthenium complexes present almost the same charge of Ru atom. Moreover, they display nearly the same structure of valence orbitals of the ruthenium. However, when it comes to compare their fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The geometry of the complete modeled eeAChE protein was compared to the X-ray structure of eeAChE (PDB ID: 1C2O) in order to confirm the methods utilized in this study, and the observed RMSD were less than 1A. Furthermore, optimization was carried out using Gaussian-16 [ 52 ] software with the WB97XD [ 53 ] level of DFT (density functional theory)/LANL2DZ [ 54 ] level of theory to minimize steric clashes in ligand structures. To find the stability of the structure, harmonic vibrational frequency analyses were carried out at the same computational level of theory.…”
Section: Methodsmentioning
confidence: 99%
“…The geometry of the complete modeled eeAChE protein was compared to the X-ray structure of eeAChE (PDB ID: 1C2O) in order to confirm the methods utilized in this study, and the observed RMSD were less than 1A. Furthermore, optimization was carried out using Gaussian-16 [ 52 ] software with the WB97XD [ 53 ] level of DFT (density functional theory)/LANL2DZ [ 54 ] level of theory to minimize steric clashes in ligand structures. To find the stability of the structure, harmonic vibrational frequency analyses were carried out at the same computational level of theory.…”
Section: Methodsmentioning
confidence: 99%